Virus-like particles vaccines based on glycoprotein E0 and E2 of bovine viral diarrhea virus induce Humoral responses - Yang, Ningning; Zhang, Jiangwei; Xu, Mingguo; Yi, Jihai; Wang, Zhen; Wang, Yong; Chen, Chuangfu (Frontiers in Microbiology, 2022)
Bovine viral diarrhea/mucosal disease (BVD/MD) is a viral infectious disease that seriously endangers the health of cattle herds and brings serious economic losses to the global cattle industry. Virus-like particles (VLPs) are empty shell structures without viral nucleic acid, which are similar to natural virus particles in morphology and structure. Because of their strong immunogenicity and biological activity, some of them have been used as vaccines in clinical trials. In this study, we developed a strategy to generate BVDV (E0+E2, E2+E2) VLPs using an insect baculovirus expression vector system (BEVS). The VLPs obtained were detected by immunofluorescence assay (IFA), western blotting analyses and transmission electron microscope (TEM), and the results showed that VLPs of high purity were obtained. Mice immunized with VLPs (15 μg) and Freund's adjuvant (100 μL) elicited higher BVDV- neutralizing antibody in comparison with Freund's adjuvant control (P < 0.0001), and even on day 21 or 35 post-prime immunization, the neutralizing antibody levels of mice immunized with E0+E2 or E2+E2 VLPs were significantly higher compared with inactivated vaccine (P < 0.05). A subsequent challenge reveals that the viral loads of livers, kidneys, spleens, lungs and small intestines were significantly lower compared with control (P < 0.0001), and the viral loads of mice immunized with E0+E2 or E2+E2 VLPs in the small intestines were significantly lower compared with inactivated vaccine (P < 0.05). Thus, VLPs are a promising candidate vaccine and warrants further clinical evaluation.